Homophobic comments on @gitasav’s instagram content for the international women’s day 2023 - Muqsith, Munadhil Abdul; Pratama, Putra Pratama; Istiyanto, S Bekti (Jurnal Studi Komunikasi, 2024)
This research aims to understand how homophobic comments on @gitasav’s Instagram account in the context of International Women’s Day 2023 are analysed using netnographic study with the application of computer-mediated communication (CMC) theory, feminist standpoint theory, and reception theory. There is a tendency for netizens to accept Gitasav’s content in her uploads celebrating International Women’s Day 2023, although, at the same time, negative comments such as insults, sarcasm, foul language, disappointment, and homophobia towards Gitasav and the LGBTQ+ community also still fill the comments section, taking the point of view that Gitasavsults from this research showed that 44% of the comments were positive, followed by 35% of neutral comments. Then the negative comments amounted to 20%. Positive negative comments were 1% and negative positive comments were 0.19%. After being classified with Reception Theory by Stuart Hall, 236 comments were in the Hegemony Dominant position, 107 comments were in the Opposition position and 8 comments were in the Negotiation position. There is a tendency for netizens to accept Gitasav’s content in her uploads celebrating International Women’s Day 2023, although, at the same time, negative comments such as insults, sarcasm, foul language, disappointment, and homophobia towards Gitasav and the LGBTQ+ community also still fill the comments section, taking the point of view that Gitasav is no longer seen as the Muslim woman she has traditionally been with LGBTQ community.